Mendeteksi Fase T Gempabumi Outer Rise Selatan Bali 18 Maret 2020 Menggunakan Seismometer Broadband dan Short – Period - I Putu Dedy Pratama; Emi Ulfiana; Pande Komang Gede Arta Negara (Buletin GAW Bariri, 2020)
Earthquakes in the outer rise area are quite rare, but have the potential for large energy accumulations and the impact of tsunamis. On 18 March 2020 an earthquake of magnitude M6.3 occurred at the epicenter coordinates of 11.4 latitude and 115.04 east longitude with a depth of 10 km. The earthquake signal of the outer rise is very interesting to study and compare the results of its recording with different sensors because it brings the T phase in its propagation. At the Denpasar Geophysics Station there is a Trilum 120P seismometer and the DS 04A short-period seismometer located side by side succeeded in recording the earthquake. The results of this recording are compared with the signal correlation to measure the correlation value between the results of the Trilium 120P recording and DS 04A. Previously the two signals were removed from the effect of the instrument response with the gain and polish values ​​of each sensor. The purpose of this study was to determine the phase T recorded on the two sensors of the Denpasar Geophysics Station. The results of this study indicate that the signal recording from broadband and Short-period seismometers show a high correlation value of 0.9963. This value increases thanks to the convolution of the influence of the instrument which previously had a correlation of 0.4536. Phase T is not visible on the signal recording in time series but appears on the spectrum <1 Hz in both Broadband and Short-period sensors.